Damage in heterogeneous aluminum alloys - Gammage, Justin J. (My University, 2002)
The role of damage on the mechanical response of a heterogeneous material was investigated through both mechanical testing and x-ray tomography. X-ray tomography was used to obtain quantitative information on the evolution of damage through processes occurring at both the local and global scale. The results indicate that heterogeneity in the spatial distribution of particles does influence the damage process. However, the influence of having one particle or more interacting with another is limited to reducing the tensile deformation required to initiate damage. The rate at which damage evolves is similar for both isolated and non-isolated particles and increasing the number of neighbors around a non-isolated particle was determined to have no additional influence on the evolution of damage. These results, coupled with mechanical testing measurements of both global and local properties, were used to develop models describing the flow response of composite materials as damage accumulates. Models were developed to predict the effects of both particle multiple cracking and micro-crack linkage on the composite flow response. The models predict that both damage processes reduce the load bearing capability of the material over that of an undamaged composite, however the loss in load bearing capability is much more severe when micro-crack linkage occurs. Micro-crack linkage rapidly leads to a loss in global stability so that the strain at which the composite fails is significantly less than previous models suggest. The experimental behavior of the composite materials investigated in the modelling work favors that predicted by the micro-crack linkage model. Ductility predictions resulting from the micro-crack linkage model were sensitive to both the volume fraction and the matrix work hardening exponent. By varying the matrix work hardening exponent the micro-crack linkage model captured the experimentally observed range of ductility values present in literature.
Keywords: Materials Science and Engineering; Materials Science and Engineering